Polynomials
Given the equation:
![x^5-3x^4+mx^3+nx^2+px+q=0](https://img.qammunity.org/2023/formulas/mathematics/college/h8vvggb1tsarubqblx46e400ubw7x2rif5.png)
Where all the coefficients are real numbers, and it has 3 real roots of the form:
![x_1=\log _2a,x_2=\log _2b,x_3=\log _2c](https://img.qammunity.org/2023/formulas/mathematics/college/n0islomkgwkvlhk0ukuft6x0p1l2mzb2rr.png)
It has two imaginary roots of the form: di and -di. Recall both roots must be conjugated.
a) Knowing the sum of the roots must be equal to the inverse negative of the coefficient of the fourth-degree term:
![\begin{gathered} \log _2a+\log _2b+\log _2c+di-di=3 \\ \text{Simplifying:} \\ \log _2a+\log _2b+\log _2c=3 \\ \text{Apply log property:} \\ \log _2(abc)=3 \\ abc=2^3 \\ abc=8 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/kggecbm5mu5bzhcdg7uks5j8k3c4f69l7s.png)
b) It's additionally given the values of a, b, and c are consecutive terms of a geometric sequence. Assume that sequence has first term a1 and common ratio r, thus:
![a=a_1,b=a_1\cdot r,c=a_1\cdot r^2](https://img.qammunity.org/2023/formulas/mathematics/college/8yxrx24x9zfcovxqkni2c5zih060mlppkc.png)
Using the relationship found in a):
![\begin{gathered} a_1\cdot a_1\cdot r\cdot a_1\cdot r^2=8 \\ \text{Simplifying:} \\ (a_1\cdot r)^3=8 \\ a_1\cdot r=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/zvh9lrhkl0gvuyjusa17cs0o1x35fgdyts.png)
As said above, the real roots are:
![x_1=\log _2a,x_2=\log _2b,x_3=\log _2c](https://img.qammunity.org/2023/formulas/mathematics/college/n0islomkgwkvlhk0ukuft6x0p1l2mzb2rr.png)
Since b = a1*r, then b = 2, thus:
![x_2=\log _22=1](https://img.qammunity.org/2023/formulas/mathematics/college/t4yzol8nuwi5w2mtu3rfzn264101yqm5mm.png)
One of the real roots has been found to be 1. We still don't know the others.
c) We know the product of the roots of a polynomial equals the inverse negative of the independent term, thus:
![\log _2a_1\cdot2\cdot\log _2(a_1\cdot r^2)\cdot(di)\cdot(-di)=-q](https://img.qammunity.org/2023/formulas/mathematics/college/93pfz2kkwqb7hnxktcvadb2piuz45fk3ym.png)
Since q = 8 d^2:
![\begin{gathered} \log _2a_1\cdot2\cdot\log _2(a_1\cdot r^2)\cdot(di)\cdot(-di)=-8d^2 \\ \text{Operate:} \\ 2\log _2a_1\cdot\log _2(a_1\cdot r^2)\cdot(-d^2i^2)=-8d^2 \\ \log _2a_1\cdot\log _2(a_1\cdot r^2)=-8 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/q5p41p0mfwz4vyarfobb9zgp7xwe6uiv8o.png)
From the relationships obtained in a) and b):
![a_1=(2)/(r)](https://img.qammunity.org/2023/formulas/mathematics/college/jj8ffu5k6z4ca1xxjgggdl1f84aa7ump8p.png)
Substituting:
![\begin{gathered} \log _2((2)/(r))\cdot\log _2(2r)=-8 \\ By\text{ property of logs:} \\ (\log _22-\log _2r)\cdot(\log _22+\log _2r)=-8 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/3ahvxny8humcqr9ja5pulzbq0rwfplwgia.png)
Simplifying:
![\begin{gathered} (1-\log _2r)\cdot(1+\log _2r)=-8 \\ (1-\log ^2_2r)=-8 \\ \text{Solving:} \\ \log ^2_2r=9 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/tf1xfq0izqcn519h06o5gkriiaafbb7v4n.png)
We'll take the positive root only:
![\begin{gathered} \log _2r=3 \\ r=8 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/7blm2bq4fsfvrf2imoyyushxczq0oy8wxx.png)
Thus:
![a_1=(2)/(8)=(1)/(4)](https://img.qammunity.org/2023/formulas/mathematics/college/izu022s1wq6db9fl4a1r5r1puyivcxa603.png)
The other roots are:
![\begin{gathered} x_1=\log _2(1)/(4)=-2 \\ x_3=\log _216=4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/39t6cxsqk6o1t5933liwjrzl3hxu2gw4j3.png)
Real roots: -2, 1, 4